Induction of 2',5'-oligoadenylate synthetase and interferon in mouse trigeminal ganglia infected with herpes simplex virus. - Sokawa, Y (1980)
The activity of 2',5'-oligoadenylate synthetase, which is induced by interferon action, was detected in mouse trigeminal ganglia infected with herpes simplex virus (HSV) type 1. When HSV was inoculated on the left cheek of mice, the virus began to appear in the ipsilateral trigeminal ganglia on day 2, reached its maximum accumulation on day 4, declined thereafter, and was no longer detected in the tissue homogenate after 11 days. After this short acute productive phase, the virus entered into the latent phase of infection. 2',5'-Oligoadenylate synthetase appeard in the trigeminal ganglia shortly after the beginning of virus multiplication; the synthetase activity began to rise on day 3, reached a maxium level on day 4, and then declined. Interferon activity (type I) also appeared in the infected ganglia, but diminished more rapidly than the synthetase. The antibody against HSV in the sera began to appear at the time when the virus and synthetase were declining. From these results it may be hypothesized, although not concluded, that in the acute productive phase of HSV infection in mouse trigeminal ganglia, virus multiplication is suppressed by interferon action, including 2',5'-oligoadenylate synthetase induction.